Reprogramming of Normal Fibroblasts into Cancer-Associated Fibroblasts by miRNAs-Mediated CCL2/VEGFA Signaling - Shen, Hua (PLoS Genet, 2016)
Cancer-associated fibroblasts (CAFs), the most common constituent of the tumor stoma, are known to promote tumor initiation, progression and metastasis. However, the mechanism of how cancer cells transform normal fibroblasts (NFs) into CAFs is largely unknown. In this study, we determined the contribution of miRNAs in the transformation of NFs into CAFs. We found that miR-1 and miR-206 were down-regulated, whereas miR-31 was up-regulated in lung CAFs when compared with matched NFs. Importantly, modifying the expression of these three deregulated miRNAs induced a functional conversion of NFs into CAFs and vice versa. When the miRNA-reprogrammed NFs and CAFs were co-cultured with lung cancer cells (LCCs), a similar pattern of cytokine expression profiling were observed between two groups. Using a combination of cytokine expression profiling and miRNAs algorithms, we identified VEGFA/CCL2 and FOXO3a as direct targets of miR-1, miR-206 and miR-31, respectively. Importantly, systemic delivery of anti-VEGFA/CCL2 or pre-miR-1, pre-miR-206 and anti-miR-31 significantly inhibited tumor angiogenesis, TAMs accumulation, tumor growth and lung metastasis. Our results show that miRNAs-mediated FOXO3a/VEGF/CCL2 signaling plays a prominent role in LCCs-mediated NFs into CAFs, which may have clinical implications for providing novel biomarker(s) and potential therapeutic target(s) of lung cancer in the future.